Enemy of the state - Scott, Tony (Pasig City : Viva Video, 1999)
Hot Hollywoed favorite Will Smith (Men in Black, Independence Day) stars with two-time Academy Award Winner Dene Hackman (Best Actor 1971, French Connection Best Supporting Actor 1992, Unforgiven) in a high-powered suspense thriller where non-stop action meets cutting code technology! Robert Clayton Dean (Smith) is a successful Washington D.C. Attorney who without his knowledge is given a video that ties a top official of the National Security Agency (Oscar Winning Best Actor Jon Voight - coming home, 1978; the rainmaker, u-turn) to a political murder! instantly, every aspect of dean's once normal life becomes targeted by a lethal team of skilled NSA surveillance operatives, who wage a relentless, ultra high-tech campaign to discredit him and retrieve the incriminating evidence! also featuring Regina King (JErry Maguire, Boyz 'n the hood) in an impressive, star-studded cast - get ready for the action to explode as dean desperately races to reclaim his life and prove his innocence... before it's too late!